Higher music education as a site of public pedagogy : Identifying institutional change in the Nordic countries - Laes, Tuulikki; Koivisto, Taru-Anneli; Sæther, Eva (Sage, 2025)
This study explores how higher music education institutions position themselves in relation to wider social and political forces and the expanding professional responsibilities of musicians in increasingly complex Nordic societies, which in this study includes Finland, Sweden, Norway and Denmark. By asking how the political—including various local and global social-ecological values, relations and power structures—is manifested in contemporary higher music performance study programs, the study aims to identify the challenges and possibilities of institutional change within higher music education in the Nordic context. Theoretically, we engage with Gert Biesta’s understanding of public pedagogy as an intrinsic part of educational endeavors that engage with the political and societal, thus promoting and serving as a catalyst for transformative change within higher music education. The data consists of five focus group interviews (n = 13) and a questionnaire (n = 29) addressed to the teachers and leaders of music performance programs in four higher music education institutions. We identified five emerging change identifications in the Nordic higher music institutions: (a) changing teacher roles, (b) students as change agents, (c) artists and/as citizens, (d) aesthetic and epistemic paradigm shifts, (5) negotiating institutional boundaries. The findings suggest that although the concept of public pedagogy is not yet fully established within these institutions, all three forms, (a) pedagogy for the public, (b) pedagogy of the public, and (c) pedagogy of publicness, are emerging. However, resistance to change could hinder higher music education from staying relevant amid current societal challenges and turbulence. By integrating public pedagogy into the daily practices and discourse of higher music education, both the necessary adaptation to political upheaval and the pedagogical and artistic identities of teachers and students could be strengthened.
Keywords: musiikkikasvatus; korkeakoulut; pedagogiikka